Analisis Implementasi Kebijakan Permendag No. 8 Tahun 2024: Dampak Terhadap Industri Tekstil dan Sektor Terkait - Prasetiyani, Erni; Saputra, Munir (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
Regulation of the Minister of Trade (Permendag) No. 8 of 2024 aims to increase the efficiency of strategic goods distribution and strengthen the domestic industry. However, the implementation of this policy faces various challenges, especially in the textile sector which is experiencing increasing production costs and decreasing competitiveness. This study uses qualitative methods with interviews and secondary data analysis to evaluate the effectiveness of this policy. The results of the study indicate that the freedom to import textiles from China without government protection greatly affects business growth and requires a more effective mitigation strategy. This study recommends policy adjustment steps so as not to hinder the growth of the industrial sector.